2017
DOI: 10.1007/s10461-017-1804-8
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From the Implementation of Seek, Test, Treat, Retain Interventions Using Mobile Phones and Text Messaging to Improve Engagement in HIV Care for Vulnerable Populations in the United States

Abstract: In the United States, little is known about interventions that rely on mobile phones and/or text messaging to improve engagement in HIV care for vulnerable populations. Domestic studies using these technologies as part of the National Institute on Drug Abuse “Seek, Test, Treat, Retain” research initiative were queried regarding intervention components, implementation issues, participant characteristics, and descriptive statistics of mobile phone service delivery. Across five studies with 1,135 predominantly ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…A recent analysis that included participants from this cohort showed that sending text messages to individuals recently released from jail likely has a negligible effect on linkage to care. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis that included participants from this cohort showed that sending text messages to individuals recently released from jail likely has a negligible effect on linkage to care. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Other study participants could not understand how to load credit onto their mobile phones or the parameters of their service plans (Smillie et al, 2014). The demographic of these study participants showed being within an economically disadvantaged group could mean that they were not able to pay for their mobile phone credit and therefore could not receive any messages (Christopoulos et al, 2017).…”
Section: Frustration Due To Technical Issuesmentioning
confidence: 97%
“…The second barrier associated with technical issues, was service interruption due to a poor credit balance as reported by Christopoulos et al, (2017), Smillie et al, (2014) and Swenderman et al, (2015). All three studies found that where participants used their own mobile phones, the inability to pay for these phones created an issue within the research.…”
Section: Frustration Due To Technical Issuesmentioning
confidence: 99%
See 2 more Smart Citations